1993
DOI: 10.1002/bjs.1800800531
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen and progesterone receptors in colorectal cancer and human colonic cancer cell lines

Abstract: Receptors for oestrogen (ER) and progesterone (PR) were assayed in tissue from 17 patients with colorectal cancer and five colonic cancer cell lines using enzyme immunoassays. ERs and PRs were detected in 15 and 17 cancers respectively, although the levels detected were low: median (range) ER 1.3 (0-11.3) and PR 3.9 (0.3-10.2) fmol per mg protein. These values were not significantly different from median (range) levels of ER (1.1 (0.6-3.0) fmol/mg) and PR (1.9 (0.5-3.2) fmol/mg) detected in normal mucosa. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Activation of the receptors can pose a downstream effect that likely leads to inhibition of cell growth. [37][38][39] Furthermore, some prior research suggests that estrogen itself is tumor suppressive and HT may enhance this relationship. For instance, methylation of the promotor region of estrogen receptor gene has been linked to human colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the receptors can pose a downstream effect that likely leads to inhibition of cell growth. [37][38][39] Furthermore, some prior research suggests that estrogen itself is tumor suppressive and HT may enhance this relationship. For instance, methylation of the promotor region of estrogen receptor gene has been linked to human colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone opposes the mitogenic effects of estrogen in reproductive tract tissues (eg, the endometrium) (26), and it is conceivable that progestagens may exert similar effects on other tissues, such as the colonic epithelium. Both normal and malignant colon cells express progesterone receptors (44)(45)(46); however, the direct biological effects of progesterone on colonic tissue are not understood. In contrast to our results, a recent study conducted in the European Prospective Investigation into Cancer (EPIC), which evaluated a similar number of colorectal cancer case subjects as in this study, found no association between reproductive history and the risk of colorectal cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that estrogen may be involved directly determining intestinal calcium absorption. Estrogen receptors (Francavilla et al, 1987;Meggouh et al, 1991;Hendrickse et al, 1993;Fernandez et al, 1996), as well as estrogen-receptor-associated proteins, pS2 antigen (Luqmani et al, 1992;Theisinger et al, 1993;Welter et al, 1994) and ER-D5 (Takeda et al, 1992), have been demonstrated consistently in the mucosa along the alimentary tract, suggesting a specific physiological role for estrogen in the intestine. Moreover, the available data indicate that the decrease in the basal levels of 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) could not solely account for the decrease in calcium absorption, suggesting that the intestine of elderly or ovariectomized women is resistant to 1,25(OH) 2 D 3 (Francis et al, 1984;Gennari et al, 1990).…”
Section: Introductionmentioning
confidence: 95%